2015
DOI: 10.1037/xhp0000143
|View full text |Cite
|
Sign up to set email alerts
|

Extending models of visual-word recognition to semicursive scripts: Evidence from masked priming in Uyghur.

Abstract: One basic feature of the Arabic script is its semicursive style: some letters are connected to the next, but others are not, as in the Uyghur word [see text]/ya xʃi/ ("good"). None of the current orthographic coding schemes in models of visual-word recognition, which were created for the Roman script, assign a differential role to the coding of within letter "chunks" and between letter "chunks" in words in the Arabic script. To examine how letter identity/position is coded at the earliest stages of word proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
7
12
0
Order By: Relevance
“…Our results are also consistent with the Uyghur data we mentioned above (Yakup et al, 2014, 2015). These authors acknowledged the role of position-dependent allography in letter position coding in skilled readers based on the finding that reading of “jumbled words” (words with internal letters rearranged) was modulated by position-dependent allography.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are also consistent with the Uyghur data we mentioned above (Yakup et al, 2014, 2015). These authors acknowledged the role of position-dependent allography in letter position coding in skilled readers based on the finding that reading of “jumbled words” (words with internal letters rearranged) was modulated by position-dependent allography.…”
Section: Discussionsupporting
confidence: 94%
“…The absence of allographic effects in Arabic as claimed by Perea et al (2013) and Carreiras et al (2012) is equally at variance with data from Uyghur, an agglutinative non-Semitic language from the Turkic family that uses an Arabic-based script in which both consonants and vowels are fully specified (Yakup, Abliz, Sereno, & Perea, 2014, 2015). Using a Rapid Serial Visual Presentation (RSVP) with sentences containing jumbled words, in which the internal letters were rearranged in a way that either did or did not lead to allographic changes, Yakup et al (2014) showed that response accuracy was significantly lower for target words in jumbled sentences involving a letter shape change, thus suggesting that position-dependent allography affects letter position coding in Uyghur.…”
Section: Previous Research On Orthographic Processing Of Arabicsupporting
confidence: 55%
“…Similarly, in a masked prime same-different experiment with individuals who mastered both the Arabic and Roman scripts, Carreiras et al (2013) found that the electrophysiological responses for Arabic letters (middle vs. isolated form) were similar to those for Roman letters (lowercase vs. uppercase); furthermore, the visual similarity effect disappeared in the P300 component in the two scripts. In addition, Yakup et al (2015) failed to find a relationship between the magnitude of masked form priming and an estimated measure of visual similarity in Uyghur (i.e., a language which is written with Arabic script). Thus, despite the obvious differences between the visual processing of words in the Roman and Arabic scripts, the underlying processes seem be, to some degree, analogous (see Okano et al, 2013; for a similar observation regarding Japanese Katakana).…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that these two languages have two distinctive features: (i) a rigid morphological structure, and (ii) vowels that are not regularly written down. Indeed, transposed-letter effects are robust in languages that use Arabic script in which vowel information is written down (e.g., Uyghur; seeYakup, Abliz, Sereno, & Perea, 2015).Psychon Bull Rev (2018) 25:416-422…”
mentioning
confidence: 99%